Protective Role of Mytilus edulis Hydrolysate in Lipopolysaccharide-Galactosamine Acute Liver Injury - Starikova, Eleonora; Mammedova, Jennet; Ozhiganova, Arina; Lebedeva, Aleksandra; Malashicheva, Anna; Semenova, Daria; Khokhlova, Evgeniia; Mameli, Eleonora; Caporali, Andrea; Wills, Jimi; Sokolov, Alexey (Frontiers in Pharmacology, 2021)
Acute liver injury in its terminal phase trigger systemic inflammatory response syndrome with multiple organ failure. An uncontrolled inflammatory reaction is difficult to treat and contributes to high mortality. Therefore, to solve this problem a search for new therapeutic approaches remains urgent. This study aimed to explore the protective effects of M. edulis hydrolysate (N2-01) against Lipopolysaccharide-D-Galactosamine (LPS/D-GalN)-induced murine acute liver injure and the underlying mechanisms. N2-01 analysis, using Liquid Chromatography Mass Spectrometry (LCMS) metabolomic and proteomic platforms, confirmed composition, molecular-weight distribution, and high reproducibility between M. edulis hydrolysate manufactured batches. N2-01 efficiently protected mice against LPS/D‑GalN‑induced acute liver injury. The most prominent result (100% survival rate) was obtained by the constant subcutaneous administration of small doses of the drug. N2-01 decreased Vascular Cell Adhesion Molecule-1 (VCAM-1) expression from 4.648±0.445 to 1.503±0.091 MFI and Interleukin-6 (IL-6) production in activated Human Umbilical Vein Endothelial Cells (HUVECs) from 7.473±0.666 to 2.980±0.130 ng/ml in vitro. The drug increased Nitric Oxide (NO) production by HUVECs from 27.203±2.890 to 69.200±4.716 MFI but significantly decreased inducible Nitric Oxide Synthase (iNOS) expression from 24.030±2.776 to 15.300±1.290 MFI and NO production by murine peritoneal lavage cells from 6.777±0.373 µM to 2.175±0.279 µM. The capability of the preparation to enhance the endothelium barrier function and to reduce vascular permeability was confirmed in Electrical Cell-substrate Impedance Sensor (ECIS) test in vitro and Miles assay in vivo. These results suggest N2-01 as a promising agent for treating a wide range of conditions associated with uncontrolled inflammation and endothelial dysfunction.